2021
DOI: 10.1155/2021/6441222
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Cooperative Learning of Language in Different Subject Lessons as Seen by Primary School Pupils: The Case of One Lithuanian City School

Abstract: Contemporary educational theory and practice promote the development of subject-specific and generic competences. Cooperative learning is a generic competence whose development is recommended in all subject lessons/activities. The development of fundamental individual values that rely not only on individual achievements but also on empathy and helping others, the ability to listen, mentor, and assist is integral to primary education. Such education is supported by positive inclusion in the process and good-wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The ideas expressed by the participants in the study on monitoring are very close to the researchers’ view that the main agreements on integrated education are made within the educational establishment (Acree et al, 2017 ; Education Development Trust. Successful school leadership , 2016 ; Jakavonytė-Staškuvienė, 2017 , 2021a , 2021b ). Importantly, a culture of “living, changing and renewing” planning is essential when working in an integrated education context: “the plan is discussed once a month, to write down changes and other proposals” (Claire).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ideas expressed by the participants in the study on monitoring are very close to the researchers’ view that the main agreements on integrated education are made within the educational establishment (Acree et al, 2017 ; Education Development Trust. Successful school leadership , 2016 ; Jakavonytė-Staškuvienė, 2017 , 2021a , 2021b ). Importantly, a culture of “living, changing and renewing” planning is essential when working in an integrated education context: “the plan is discussed once a month, to write down changes and other proposals” (Claire).…”
Section: Resultsmentioning
confidence: 99%
“…Successful school leadership , 2016 ). Research has shown that the role of the teacher is one of the most important factors and variables in the development of an integrated curriculum, as the teacher influences students (according to Hattie, 2009 ; Jakavonytė-Staškuvienė, 2021a , 2021b ). Researchers Hattie ( 2009 ), Bressoux ( 2012 ) and Talbot ( 2007 ) stress that cognitive and motivational stimulation, participation, engagement and deliberate timing of the teacher’s task remain important in the design of classroom activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the ways to foster students' self-directed learning skills is through collaboration [28][29][30][31], as it enhances children's ability to act and create knowledge themselves. Collaborative social sharing practices in schools allow students to acquire a significant amount of knowledge by solving problems, constructing, and transforming what is common.…”
Section: Independent and Self-directed Learning Paradigmsmentioning
confidence: 99%
“…Then, the class group of students becomes the audience. It also allows students to help each other, learn to collaborate, and participate in discussions or debates by presenting ideas and arguing various points [26,[28][29][30][31]. When a collaborative atmosphere that supports teamwork skills is created, children can assess their abilities and acknowledge that under such conditions, they can work and learn new things [29,30].…”
Section: Independent and Self-directed Learning Paradigmsmentioning
confidence: 99%